The prevalence, child characteristics, and maternal risk factors for the continuum of fetal alcohol spectrum disorders: A sixth population-based study in the same South African community. (1st January 2021) - May, Philip A.; Marais, Anna-Susan; De Vries, Marlene M.; Buckley, David; Kalberg, Wendy O.; Hasken, Julie M.; Stegall, Julie M.; Hedrick, Dixie M.; Robinson, Luther K.; Manning, Melanie A.; Tabachnick, Barbara G.; Seedat, Soraya; et al.
Highlights: The rate of total FASD in this community was high in 2014, 16–30 %. The rate of fetal alcohol syndrome was 4.3–6.6 %, similar to that in 1999. As few as 2 drinks per drinking day was significantly associated with FASD diagnoses. Two days per week was the modal drinking frequency reported for FASD diagnoses. Drinking in all trimesters increased the odds of FASD to 19 times that of abstinence. Abstract: Background: Prevalence and characteristics of fetal alcohol spectrum disorders (FASD) have been described previously in this community. Methods: Active case ascertainment methods were employed in a new cross-sectional study with Revised Institute of Medicine criteria among first grade students ( n = 735) via dysmorphology examinations and neurobehavioral assessments. Their mothers were interviewed regarding risk factors. Final diagnoses were assigned via structured case conferences. Results: Children with fetal alcohol syndrome (FAS), partial FAS (PFAS), and alcohol related-neurodevelopmental disorder (ARND) were significantly different from controls on all cardinal variables, multiple dysmorphology traits and neurobehavioral performance. Mothers of children with FASD reported significantly more drinking before and during pregnancy (mothers of children with FAS reported 7.8 (±6.1) drinks per drinking day (DDD) prior to pregnancy and 5.1 (±5.9) after pregnancy recognition). Distal risk variables for a diagnosis on the continuum of FASD were: lower maternal height, weight, and body mass index; higher gravidity; lower education and household income; and later pregnancy recognition. Alcohol and tobacco remain the only commonly used drugs. Women reporting first trimester drinking of two DDD were 13 times more likely (95 % CI:1.3-133.4) to have a child with FASD than non-drinkers; and those who reported drinking throughout pregnancy were 19.4 times more likely (95 % CI:8.2–46.0) to have a child with FASD. Conclusion: Seventeen years after the first study in this community, FASD prevalence remains high at 16 %–31 %. The FAS rate may have declined somewhat, but rates of PFAS and ARND seemed to plateau, at a high rate.